Założenie spójności semantycznej systemu prawa w klaryfikacyjnej teorii wykładni - Pulka, Zbigniew (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The author assumes that a clarificatory theory of interpretation may be counted as a theory which directly expresses a philosophical attitude consisting in acceptance of the main assertions of Marxism as a logically prior presuppositions of the theoretical cognition of the legal phenomena. Especially, logically prior Marxism is to determine fundamental values accepted by the legal theory.Marxian axiology recognizes social unity as a fundamental value. This value transferred to the legal theory takes shape of the unity of the legal system. An especially important form of unity of the legal system is its semantic coherence. The author tends to point out that in the clarificatory theory of interpretation the assumption of semantic coherence of the legal system is expressed by the directive called “presumption of the legal language.” According to this directive, if the meaning of the phrase is determined by the legal language, such meaning should be accepted as binding in the whole legal system, i.e. in all branches of the legal system. The author treats this directive as a result of the impact of logically prior philosophical assumptions on the theory of legal interpretation.
Keywords: semantic coherence; legal system; theory of law; interpretation